Freedom's ordeal : the struggle for human rights and democracy in post-Soviet states - Juviler, Peter H. (Pennsylvania studies in human rights., 1998)
Fifteen countries have emerged from the collapse of the Soviet Union. Freedom's Ordeal recounts the struggles of these newly independent nations to achieve freedom and to establish support for fundamental human rights. Although history has shown that states emerging from collapsed empires rarely achieve full democracy in their first try, Peter Juviler analyzes these successor states as crucial and not always unpromising tests of democracy's viability in post-communist countries. Taking into account the particularly difficult legacies of Soviet communism, Freedom's Ordeal is distinguished by its careful tracing of the historical background, with special attention to human rights before, during, and after communism. Juviler suggests that the culture and practices of despotism may wither wherever modernization conflicts with tyranny and with the curtailment or denial of democratic rights and freedoms.